Strategic framework construction for sustainable livelihood of livestock farmers in drought prone areas: A participatory approach from Odisha - Patnaik, Neela Madhav; Meena, Brajendra Singh; Maji, Saikat; Kar, Priyajoy (Indian Journal of Dairy Science, 2022)
Livestock rearing is a critical component for ensuring sustainable livelihood particularly in drought prone areas. A participatory research was undertaken in drought affected region of Odisha. The state of Odisha was purposively selected due to the incidence of severe drought occurrences predominantly in the western parts of the state. For undertaking this participatory research, two districts Balangir and Nuapada were selected randomly from the drought prone districts. The objective of the study was to construct a framework of strategies in consultation with famers and other stakeholders of livestock sector. To attain the objective, the qualitative study involved focus group discussions in four randomly selected villages from Balangir and Nuapada in addition to transect walk. Exploratory research design was followed in carrying out this research study. The key problems identified by the stakeholders were segregated into dimensions of breeding, feeding and healthcare management and ranked within each dimension. Some of the key problems found in the study area were anestrus, repeat breeding, lack of pasture grass for grazing and high susceptibility to diseases and decreased feed intake. Appropriate strategies were formulated against each problem which can be carried out at farm and community level by the livestock farmers to mitigate the drought impacts and a sustainable livelihood.